The lost continent - Sutherland, Tui T. (Wings of fire, 2018)
Blue the SilkWing is content. Life in his Hive is safe; he loves his family; he has enough to eat. And Pantala has been at peace for as long as he can remember -- SilkWings and HiveWings live and work together in harmony, and because they stay vigilant, no one has seen a dangerous LeafWing in years. Now that Blue's sister, Luna, is undergoing her Metamorphosis, Blue knows things are going to change. Luna will have her wings and her silk, be assigned a partner and a work order, and move to another Hive. A few days later, Blue's own wings and silk will come in. But nothing could prepare Blue for what happens when Luna's wings start to grow. Suddenly his world is turned upside down, throwing him into dangers he never knew existed. Pantala isn't as peaceful as it seems, and Blue isn't safe. Whether he's ready or not, it's time to adapt -- and fight for his life.